"It's Not a Pattern of Behavior": Proxy Deflection of Eviction Stigma by Community Care Providers. Issue 3 (24th August 2020) - Grainger, Garrett L.
Abstract : Community care is the "hospital without walls" model of mental health services that deinstitutionalized mental patients in the late‐twentieth century. Neoliberal reforms have challenged the implementation of community care by restricting access to permanent housing. Extreme poverty has rendered eviction commonplace for community care recipients. The mark of an eviction limits lease attainment. As a result, community care providers practice proxy deflection—redemption, externalization, and paternalism—to resist eviction stigma during the leasing process. This paper extends stigma research by examining resistance rather than imposition of stigma by social service providers, contextualizing resistance with the perspective of stigmatizers, and identifying resources that proxy resistance offers service recipients leasing up in stratified private rental markets during the neoliberal era.